SOCIALISATION OF SMEs DEVELOPMENT BY INTRODUCING THE ROLE OF DIGITAL MARKETING FOR WOMEN PKK IN SERANGREJO HAMLET - Kusumaningrum, Betty; Hadi, Syamsul; Nurmala, Ika; Sheidu, Comfort Fatimoh (SMARTINDO, 2023)
Technological progress is something that cannot be avoided in today's life, because technological progress will run in line with scientific progress, Current technological developments have shown many extraordinary advances. Many things in the life sector have used the existence of technology itself. One of the economic forces that has been supporting the Indonesian state economy and regional economic strength is the presence of micro, small and medium-sized enterprises (MSMEs). Micro, Small and Medium Enterprises (MSMEs) must be able to compete in international markets so as not to be oppressed. Moreover, in this competitive era, MSME players should be aware of information technology (IT) so that they can make it easier to market products outside the region and abroad. Digital marketing has become one of the media that is often used by business people because of the new ability of consumers to follow the flow of digitalization, several companies are little by little starting to abandon conventional marketing models and switch to modern marketing. Based on the description above, we can conclude that digital marketing is very important in MSMEs. In KKN activities in Kulwaru Padukuham Serangrejo Village, where in their activities there are still many business actors who do not know and how to use digital marketing, especially marketplaces, this can be caused by various factors that occur, one of which is environmental factors. So the author held socialization activities for MSME Development by Introducing Digital Marketing in order to improve the economy in Padukuhan Serangrejo.